2015
DOI: 10.1586/14737167.2015.1044514
|View full text |Cite
|
Sign up to set email alerts
|

The use of adalimumab, etanercept, golimumab and infliximab in rheumatic pathologies: variation between label dosage and real-world use

Abstract: Rheumatoid arthritis (AR), psoriatic arthritis (PSA) and ankylosing spondylitis (AS) are autoimmune systemic diseases characterized by inflammation, pain and joint degeneration. The objective of this study is to evaluate, under the actual conditions of use, dosing patterns of adalimumab, etanercept, golimumab and infliximab in these pathologies, and compare them with the label regimens recommended, as well as evaluating the financial implications of these regimen modifications. The study population included al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…These results were consistent with a previous study that found that patients with AS often required dose increases of infliximab [27]. Although the reasons for the more frequent dose escalations with infliximab are not entirely understood, possible reasons include specific dosing instructions, caution in administering the initial dose(s), increased flexibility of iv.…”
Section: Add-on Medication N (%)supporting
confidence: 91%
“…These results were consistent with a previous study that found that patients with AS often required dose increases of infliximab [27]. Although the reasons for the more frequent dose escalations with infliximab are not entirely understood, possible reasons include specific dosing instructions, caution in administering the initial dose(s), increased flexibility of iv.…”
Section: Add-on Medication N (%)supporting
confidence: 91%
“…Currently, an overview of the guidelines in individual European countries and the changes therein over time does not exist. Examples of differences between countries are different initial doses and/or step up strategies,20–22 comedication with csDMARDs23–25 and mandatory elevation of CRP or evidence of inflammation on MRI for patients with nr-axSpA 26. Those differences in access to therapy and treatment guidelines between countries probably account for some of the variation in both baseline variables and treatment outcomes observed in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…Collaboration across registries may provide knowledge regarding prescription patterns, which has an interest in its own, but may also allow for investigation of heterogeneity across countries. The differences in prescription patterns and access to treatment imply that the results of pooling of data across countries should be interpreted with caution 20…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that optimizing bDMARD therapy via off-label dosage for patients with rheumatic diseases is becoming more routine [1214]. Limited research has been conducted to support long-term health outcomes associated with patterns of bDMARD utilization in the symptom management of PsA [3, 4, 12, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Limited research has been conducted to support long-term health outcomes associated with patterns of bDMARD utilization in the symptom management of PsA [3, 4, 12, 15, 16]. Off-label dosages (i.e., dose escalation or reduction, interrupted treatment) have been shown to occur in clinical practice for the treatment of other inflammatory conditions, such as psoriasis (PsO) and rheumatoid arthritis (RA) [8, 13, 1720].…”
Section: Introductionmentioning
confidence: 99%